Investigations on the thermal response of a solid rocket motor with complex charge structure using CL-20/GAP propellant - Yiyao Wang; Junjie Wen; Junsen Yang; Guanglong Zhang; Ningfei Wang; Yi Wu (Case Studies in Thermal Engineering, 2022)
The thermal safety of a solid rocket motor with a complex charge structure using CL-20 (Hexanitrohexaazaisowurtzitane)/GAP (Glycidyl Azide Polymer) propellant was evaluated. The morphology and thermal decomposition properties of the propellant were first studied by differential thermal analysis, thermogravimetric analysis and scanning electron microscopy experiments. A numerical model of cook-off for a solid rocket motor using GAP/CL-20 propellant was developed. This model takes into account the entire process of cooking off, i.e., the thermal decomposition before ignition and the combustion reaction after ignition. The model is verified, and the kinetic parameters are determined by bomb cook-off experiments. Comparisons between experiments and simulations show that the developed model can accurately predict the thermal response of the propellant. The cook-off processes of a 3D-solid rocket motor with complex charge structures are then simulated with different heating rates. It shows that the charge structure and the annular area of the motor casing play an import role in the ignition location of the propellant. Meanwhile, the heating rate has a dramatic effect on the ignition time. The reaction intensity after the ignition of the solid rocket motor using the GAP/CL-20 propellant is more intense than those using HTPE (hydroxyl-terminated polyether)/HTPB (Hydroxyl-terminated polybutadiene) propellant.